Preliminary effects of carbon monoxide feedback module (COQUIT) on motivation to quit among college students in Selangor - Zainal Abidin, Muhammad 'Adil; Kadir@Shahar, Hayati; Abdul Manaf, Rosliza (2019)
Background: Carbon monoxide analyzer is widely being used in smoking cessation for evaluating smoking abstinence. However, it can also be utilise to motivate intention to quit among smokers. A biomedical risk feedback module was developed based on carbon monoxide analyzer to motivate smoker’s motivation to quit.